A revision of the genus Seeversiella Ashe, 1986 (Coleoptera: Staphylinidae: Aleocharinae) - Gusarov, Vladimir I. (Zootaxa, 2003)
The Nearctic and Neotropical genus Seeversiella Ashe, 1986 is redescribed. Twenty seven new species of Seeversiella are described (S. texana Gusarov, sp. n. from Texas, S. sonomotoides Gusarov, sp. n. and S. liliputana Gusarov, sp. n. from Arizona, S. fusca Gusarov, sp. n., S. tuberculicauda Gusarov, sp. n., S. nigriceps Gusarov, sp. n. and S. mexicana Gusarov, sp. n. from Mexico, S. castanea Gusarov, sp. n. from Mexico and Honduras, S. grandis Gusarov, sp. n. from Guatemala, S. badia Gusarov, sp. n. and S. minima Gusarov, sp. n. from El Salvador, S. similis Gusarov, sp. n. from Honduras, S. brunnea Gusarov, sp. n., S. curtipennis Gusarov, sp. n., S. lativentris Gusarov, sp. n., S. luridicollis Gusarov, sp. n., S. micralymma Gusarov, sp. n., S. impressicollis Gusarov, sp. n., S. sulcicollis Gusarov, sp. n., S. microphthalma Gusarov, sp. n., S. geostiboides Gusarov, sp. n., S. adusta Gusarov, sp. n., S. flavida Gusarov, sp. n. and S. paramoana Gusarov, sp. n. from Costa Rica, S. scabricollis Gusarov, sp. n. and S. furcativentris Gusarov, sp. n. from Costa Rica and Panama, S. brevipennis Gusarov, sp. n. from Panama). Atheta globicollis Bernhauer, 1907 (distributed from southern Canada to Honduras) is transferred to Seeversiella and redescribed. Seeversiella bispinosa Ashe, 1986 is placed in synonymy with S. globicollis. A key for identification of species of Seeversiella is provided. The lectotype of Atheta globicollis Bernhauer, 1907 is designated. Geographical distribution of Seeversiella is discussed.